2017
DOI: 10.1001/jamapsychiatry.2016.3578
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Major Depressive Disorder in Han Chinese Women

Abstract: IMPORTANCE Despite the moderate, well-demonstrated heritability of major depressive disorder (MDD), there has been limited success in identifying replicable genetic risk loci, suggesting a complex genetic architecture. Research is needed to quantify the relative contribution of classes of genetic variation across the genome to inform future genetic studies of MDD. OBJECTIVES To apply aggregate genetic risk methods to clarify the genetic architecture of MDD by estimating and partitioning heritability by chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 36 publications
3
44
0
1
Order By: Relevance
“…In the CONVERGE sample, was reported as 20-29%. 128 Its r g with the seven European MDD cohorts was 0.33 (SE 0.03). 129 For comparison, r g for CONVERGE with European results for schizophrenia was 0.34 (SE 0.05) and 0.45 (SE 0.07) for bipolar disorder.…”
Section: Methodsmentioning
confidence: 93%
“…In the CONVERGE sample, was reported as 20-29%. 128 Its r g with the seven European MDD cohorts was 0.33 (SE 0.03). 129 For comparison, r g for CONVERGE with European results for schizophrenia was 0.34 (SE 0.05) and 0.45 (SE 0.07) for bipolar disorder.…”
Section: Methodsmentioning
confidence: 93%
“…The for depressive symptoms from the total sample was 0.04 (s.e. 0.004), which is considerably lower than the estimates from clinically ascertained MDD samples (~0.2 in both the PGC and CONVERGE studies) [9, 27]. This may result from mixing heterogeneous measures of depression which are influenced by different combinations of genetic variants and the weak information on depression symptoms from just two questions.…”
Section: Social Science Genetic Association Consortiummentioning
confidence: 87%
“…Dr. Kendler reported that they successfully detected and replicated two common variants contributing to MDD risk on chromosome 10q: upstream of SIRT1 and in an intron of LHPP (Converge Consortium, 2015). He also commented on the genetic architecture of MDD, reporting that (1) genome-wide SNP-based heritability was estimated as 21-28%, (2) the heritability in MDD explained by each chromosome was proportional to its length (r=0.680) thus supporting a highly polygenic etiology, (3) the variance explained was distributed across the allelic frequency spectrum, (4) partitioning by genic annotation indicated a greater contribution of SNPs in coding regions and within the 3′-UTR regions, and (5) that DNase hypersensitive sites in many cell types including brain-related cells were enriched for associations with MDD (Peterson et al, submitted to Mol Psychiatry ).…”
Section: Introductionmentioning
confidence: 95%